Variables de Control en un modelo de desarrollo con autoorganización: análisis de políticas económicas con presupuesto equilibrado - London, Silvia (Estudios de Economía, 2016)
The decades of 1950 and 1960 were the heyday of the Theory of Economic Development. Later on, difficulties in modeling the complex features of the development process and the failure of the policies recommended on the basis of the theory lead to the virtual demise of this area of research. The 1990s brought about a change in this trend, particularly due to the introduction of new features into the analysis of development processes. So, the renewed interest in the nature of complementarities and externalities, together with the emphasis on non-linear models as well as on the institutional features of economies, lead to a fresh insight into the older presentations of Development Economics. In this line, this work presents a discussion about certain formal tools that we think will become handy in the analysis of development phenomena. We present a non-linear model of development, on which we perform a causality analysis, in order to identify variables that could be selected as candidates to the application of control. This could help in the design of political economies. In fact, in the paper we present a specific example of a policy intended to induce a fast development while keeping a balanced budget. Since in our model the nonlinearities lead to self-organization, analytical solutions are not available. Therefore, we run simulations to show the results of using different control variables for the development process. It becomes evident that the variables detected in our causality analysis perform better. We draw from this fact general conclusions that we think may apply to every branch of Development Theory.